Relationship between Albumin Levels and the Incidence of Ascites in Patients with Liver Cirrhosis - Vesri Yoga; Arnelis; Nasrul Zubir; Saptino Miro; Andry Kurniawan (HM Publisher, 2023)
Background: Patients with cirrhosis often develop hypoalbuminemia. In conditions of hepatic dysfunction, albumin synthesis is decreased due to hepatic dysfunction and abnormal distribution of portal blood flow. Ascites is a major complication and an important sign in the course of cirrhosis and is associated with 50% mortality after two years. 75% of patients' ascites etiology is liver cirrhosis, 10% malignancy, 3% heart failure, 2% tuberculosis, 1% pancreatitis, and others. Methods: This cross-sectional study was conducted from the medical records of patients with liver cirrhosis who were treated at the internal medicine section of Dr. M Djamil General Hospital, Padang, in 2015-2020. Patients with heart defects, malignancy, tuberculosis, pancreatitis, kidney failure, and incomplete medical record data were excluded from the study. Patients were grouped according to the presence or absence of ascites and albumin levels. Analysis using the chi-square test in 2020. Results: From 225 cases, 103 cases were analyzed. 77 were men (74.8%), and 26 were women (25.2%). The age of the patient was in the range of 40-60 years. No ascites were found in 30 people (29.1%), and 73 people (70.9%) had ascites. From normal albumin levels, five were without ascites, and four were with ascites. On mild hypoalbumin, 13 had no ascites, and 38 people had ascites. On severe hypoalbumin, 12 people were without ascites and 31 with ascites. A chi-square test was analyzed, and it was found that there was no relationship between the incidence of ascites and albumin levels (p 0.182). Conclusion: The incidence of ascites is not related to blood albumin levels.